The cost of cool youth, consumption and the environment - Molina, Gregory (San Francisco : The Video Project, 2001)
This video looks at everyday items, from T-shirts to sneakers, and tracks the effect of their manufacture on the world's resources
Executive producer, Alexandra Paul...[et. al]
Host: Alexandra Paul
VHS format
Keywords: Consumption (Economics).; Consumer goods